Leadership skills of school heads as perceived by the teachers in the selected divisionschools in antipolo city : basis for policy formulation - Panganiban, Jr. , Rufino L. (Manila : National University, 2014)
All schools have its own goal and of course have their own leaders. A leader who is passionately loves his dedication in the so-called "calling in teaching". Being a teacher or School head needs to have different good attitudes every situation. The leadership skills might be one of the contributory factors to have an effective school.
Title page -- Approval Sheet -- Acknowledgement -- Dedication -- Abstract -- Table of contents -- List of tables -- List of figures -- Chapter 1. The Problem and its setting -- Chapter 2. Review of related literature and studies -- Chapter 3. Research Design and Methodology -- Chapter 4. Presentation, Analysis, and Interpretation of Data -- Chapter 5. Summary, Conclusion, and Recommendation -- Bibliography -- Appendices -- Curriculum Vitae.
Research Method : Descriptive Method.
Includes bibliographical references.